THE 3-DIMENSION PICTURES IN INCREASING THE STUDENTS ABILITY AND INTEREST TO WRITE DESCRIPTIVE COMPOSITION - Asrifan, Andi; Rinantanti, Yulini; Tang, Syamsu; Nadirah, Nadirah (JOURNAL OF ADVANCED ENGLISH STUDIES, 2019)
The aim of conducting this research are to find out whether or not using 3-Dimensional pictures is able to increase the ability of the students of SMP Negeri 3 Pangsid Kabupaten Sidenreng Rappang to write a descriptive composition. And to find out whether or not the use of 3-Dimensional pictures is interesting for the students in writing English. In this research, the researcher employed a cluster random sampling technique meaning two classes from five classes in the population were taken as the sample which represented the experimental and control group. The classes were selected randomly. The number of total samples was 60 students. The researcher used two kinds of instruments in collecting data namely writing test and questionnaire and calculating the mean score, standard deviation, frequency table, and the value of t-test to identify the difference between pretest and posttest by using inferential analysis in SPSS 21.0 program for the windows evaluation version. To calculate questionnaire data into a percentage, the researcher used the percentage technique using this SPSS 21.0 program for the windows evaluation version. The result of the research shown that the use of 3D-Pictures as an authentic material can improve the students’ writing ability. The writing ability of students who used 3D-Pictures as an authentic material and those who had just used conventional way had a significant difference. Therefore, it could be concluded that the Eighth-grade students’ of SMP Negeri 3 Pangsid Kabupaten Sidenreng Rappang have better writing ability by using 3D-Pictures as authentic material. And the use of 3D Pictures in teaching process particularly in writing skill was interesting and effective. It was proved by a mean score of students answer in the questionnaire showed that the students were categorized as interested.